2020
DOI: 10.1016/j.isci.2020.101645
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Infection Dysregulates the Metabolomic and Lipidomic Profiles of Serum

Abstract: COVID-19 is a systemic infection that exerts significant impact on the metabolism. Yet, there is little information on how SARS-CoV-2 affects metabolism. Using NMR spectroscopy, we measured the metabolomic and lipidomic serum profile from 263 (training cohort) + 135 (validation cohort) symptomatic patients hospitalized after positive PCR testing for SARS-CoV-2 infection. We also established the profiles of 280 persons collected before the coronavirus pandemic started. PCA analyses discriminated both cohorts, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
194
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(264 citation statements)
references
References 31 publications
(28 reference statements)
43
194
1
2
Order By: Relevance
“…We found a differential metabolomic profile of recovered COVID-19 patients compared with pre-pandemic controls and severe COVID-19 patients. Consistent with previous reports, ours confirmed that COVID-19 patients are characterized by lipid dysregulation in fatty acids, glycerophospholipids, glycerolipids, and sphingolipids, which has been associated with dyslipidemia and oxidative stress [ 30 , 31 ]. Recovered patients regulated the most prominent metabolic perturbations that were associated with SARS-CoV-2 infection on metabolic function, such as a decrease in lipid levels, along with an increase in ketone bodies.…”
Section: Discussionsupporting
confidence: 92%
“…We found a differential metabolomic profile of recovered COVID-19 patients compared with pre-pandemic controls and severe COVID-19 patients. Consistent with previous reports, ours confirmed that COVID-19 patients are characterized by lipid dysregulation in fatty acids, glycerophospholipids, glycerolipids, and sphingolipids, which has been associated with dyslipidemia and oxidative stress [ 30 , 31 ]. Recovered patients regulated the most prominent metabolic perturbations that were associated with SARS-CoV-2 infection on metabolic function, such as a decrease in lipid levels, along with an increase in ketone bodies.…”
Section: Discussionsupporting
confidence: 92%
“…The bio-fluid analysed, the number of samples, the platform used and the main altered lipid species are shown. Bio-fluid N. of samples Platform Main altered lipids Reference Serum 108 High-Res MS Glycerophospholipids Shen et al [ 136 ] Serum 50 QQQ GM3s, free fatty acids Song et al [ 137 ] Plasma 35 QQQ NEFAs, TAGs, PCs Wu et al [ 148 ] Serum 57 QQQ PUFAs and lipid mediators Schwarz et al [ 141 ] Plasma 161 High-Res MS PCs, LPCs, PEs, LPEs, NEFAs Barberis et al [ 144 ] Serum 49 High-Res MS Acylcarnitines, NEFAs Thomas et al [ 138 ] Serum 236 NMR Short chain fatty acids Bruzzone et al [ 146 ] Plasma 102 High-Res MS and QQQ TAGs, PCs Overmyer et al [ 145 ] …”
Section: Dysregulation Of Lipids In Covid-19 Diseasementioning
confidence: 99%
“…Finally, lipids alterations were detected using NMR spectroscopy by Bruzzone et al [ 146 ]. The authors analysed 263 symptomatic patients, and they found a pathogenic rearrangement of the lipoprotein particle size and composition.…”
Section: Dysregulation Of Lipids In Covid-19 Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Also, higher increase of 2-hydroxybutyric acid (an indication of hepatic glutathione synthesis and oxidative stress marker). So, SARS-CoV-2 infection caused liver damage correlated with dyslipidemia and oxidative stress[ 71 ]. The viral infection is depended on the lipid metabolism of the infected cells.…”
Section: Covid-19 and Lipidomementioning
confidence: 99%